Robust control of active suspension system for a quarter car model - Md. Sam, Yahya (Universiti Teknologi Malaysia, 2006)
The aims of this research are to establish the nonlinear mathematical model and the robust control technique of the hydraulically actuated active suspension system for a quarter car model. The purpose of a car suspension system is to improve riding quality while maintaining good handling characteristics subject to different road profile. A new nonlinear quarter car model, which incorporates the rotational motion of the wheel and the dynamics of the control arm, is used in this research . The proposed controller consist of two controller loops namely inner loop controller for force tracking control of the hydraulic actuator and outer loop controller to reject the effects of road induced disturbances. The outer loop controller utilized a proportional integral sliding mode control (PISMC) scheme. Whereas, proportional integral (PI) control is used in the inner loop controller to track the hydraulic actuator in such a way that it able to provide the actual force as close as possible with the optimum target force produced by the PISMC controller. A simulation study is performed to proof the effectiveness and robustness of the control approach. The performance of the controller is compared with the LQR controller and the passive suspension system. Force tracking performance of the hydraulic actuator is also investigated. The simulation is enhanced with 3-D animation of the car going on a road bump.